1970
DOI: 10.2307/1218949
|View full text |Cite
|
Sign up to set email alerts
|

AMINO ACID SEQUENCE STUDIES OF PLANT CYTOCHROMES c

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. International Association for Plant Taxonomy (IAPT)is collaborating with JSTOR to digitize, preserve and extend access to Taxon. SummaryThe amino acid sequence of mung bean an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1971
1971
1983
1983

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Many other cytochromes c have an identical sequence (-Gly-Arg-Lys-Thr-Gly-) to Asterias in the region 37-41, but no similar anomalous cleavage has been reported [1,2], although partial hydrolysis at threonine-40 was reported in human [13]. However, the activity of TPCK-trypsin at tyrosine-97 of cytochrome c is quite common and may be due to a less than complete ethanolic denaturation coupled with the position of this residue in the three-dimensional structure of the molecule [14,15].…”
Section: Discussionmentioning
confidence: 98%
“…Many other cytochromes c have an identical sequence (-Gly-Arg-Lys-Thr-Gly-) to Asterias in the region 37-41, but no similar anomalous cleavage has been reported [1,2], although partial hydrolysis at threonine-40 was reported in human [13]. However, the activity of TPCK-trypsin at tyrosine-97 of cytochrome c is quite common and may be due to a less than complete ethanolic denaturation coupled with the position of this residue in the three-dimensional structure of the molecule [14,15].…”
Section: Discussionmentioning
confidence: 98%
“…In view of the fact that relatively few animal vertebrate cytochrome c sequences had been successfully used to construct a phylogenetic tree which corresponded to the fossil data, Boulter et al (1970) concluded at that time that "if the present potential of the method continues to be realised it is hoped to establish the major branches of a phylogenetic tree for the plant kingdom in the future". In view of the fact that relatively few animal vertebrate cytochrome c sequences had been successfully used to construct a phylogenetic tree which corresponded to the fossil data, Boulter et al (1970) concluded at that time that "if the present potential of the method continues to be realised it is hoped to establish the major branches of a phylogenetic tree for the plant kingdom in the future".…”
Section: Introductionmentioning
confidence: 99%